Changing Investment scenario in 21st Century with special referenceto Small investorsin India (International Journal of Food and Nutritional Sciences, 2022)
Investment refers to the parting the benefit today in anticipation of getting more benefit in the future period. Investment decision is very important decision not only for big organizations but also for small investor. Investment is considered as one of the most important aspect of the financial palnning.Common man invests his hard earn money in different ways in anticipation of its appreciation. For taking such decision it requires adequate knowledge in respect of risk involved in the decision and earning from such investment. Common investor always consider three important factors before investing viz. liquidity, profitability and safety of the investment. This paper tries to focus various objectives behind the investment decision of a small investor as well as how the investment pattern of small investors is changing from traditional ways of investing to tapping the newer investment opportunities in search of getting maximum returns as well as what are the threats to the common investor in the market.